ANTIMICROBIAL RESISTANT PATTERN OF SALMONELLA TYPHI ISOLATED FROM CHILDREN (Journal of Medical & Health Sciences Review, 2025)
The aim of this research was to investigate the prevalence of multidrug-resistance and extensively drug-resistance Salmonella (S.) Typhi isolated from the blood samples from children having typhoid. S. Typhi has developed resistance against first line of drugs (MDR), in addition with fluoroquinolones and 3rd generation of drugs cephalosporins (XDR). Aseptically a total of 130 samples were collected from four different hospitals and clinics. Typhoid positive samples were inoculated in blood culture broth. Antimicrobial susceptibility testing was performed by using modified method of Kirby-Bauer disc diffusion and results were compared according to CLSI manual. The bacteria were investigated against different antibiotics. Majority of the S. Typhi were extensively drug resistant but some samples showed unusual antibiogram pattern where resistant to all tested antibiotics except trimethoprim-sulfamethoxazole and tetracycline was observed. Data was analyzed statistical analysis and percentage positivity was recorded for culture positive and resistant serovar of S. enterica (S. Typhi). Out of 50 samples 10% (14 samples) were positive for S. Typhi isolates. Kirby Bauer's disc diffusion assay of these 14 samples was performed to evaluate antibiogram pattern and observed that 28.57% of S. Typhi isolates were highly resistant to first line of medication on the basis of which they were regarded as MDR S. Typhi. 50% of the samples were resistant to first and second line of drugs and were regarded as XDR S. Typhi. 21.42% samples showed resistant to all tested antibiotics conferring a very unusual antibiogram pattern. This study showed the increased prevalence of resistant S. Typhi in children.